2020
DOI: 10.3802/jgo.2020.31.e26
|View full text |Cite
|
Sign up to set email alerts
|

How to predict treatment failure in frail patients with advanced epithelial ovarian cancer: strategies to personalize surgical effort

Abstract: How to predict treatment failure in frail patients with advanced epithelial ovarian cancer: strategies to personalize surgical effort ► See the article "Characteristics and survival of ovarian cancer patients treated with neoadjuvant chemotherapy but not undergoing interval debulking surgery" in volume 31, e17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Even so, patients with optimal cytoreduction in PDS had a better prognosis in the majority of studies 7 . Nevertheless, NAC has been proposed as an alternative for patients with AOC with an excessively high fragility index for PDS 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Even so, patients with optimal cytoreduction in PDS had a better prognosis in the majority of studies 7 . Nevertheless, NAC has been proposed as an alternative for patients with AOC with an excessively high fragility index for PDS 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%
“…This finding contradicts current arguments towards the value of surgery in advanced ovarian cancer, which claim that it is mainly the tumour biology that dictates survival and also operability and not actual surgical effort. 6 , 27 Our data indicate that tumour debulking is an important factor for patient survival and maximal surgical effort can shift the patients towards a more favourable prognosis group.…”
Section: Discussionmentioning
confidence: 75%
“…Currently, all surgical decision-making processes are based mainly on infrastructural, clinical and fragility parameters as well as factors related to surgical philosophy and training. 6 …”
Section: Introductionmentioning
confidence: 99%
“…The main reasons identified were extent of disease not amenable to surgery or lack of response to NACT, patient co-morbidities preventing surgery and extent of disease. The patients who did not have debulking surgery, had an over 3-fold increase in mortality of any cause, compared to those who had surgery at some point [31,32].…”
Section: Clinical Assessmentmentioning
confidence: 95%
“…absence of lung or multiple parenchymal liver metastases on the CT scan. Liu et al [31,32] reported that more than a quarter of women with advanced ovarian cancer treated with neoadjuvant chemotherapy (NACT) do not ever undergo cytoreductive surgery. Significant risk factors contributing to the inability to undergo surgery were advanced age, low albumin levels, frailty scores and extensive disease of predominantly high-grade serous histology.…”
Section: Clinical Assessmentmentioning
confidence: 99%